2016
DOI: 10.1007/s11104-015-2771-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of litter layer to soil greenhouse gas emissions in a temperate beech forest

Abstract: Background and aims The litter layer is a major source of CO 2 , and it also influences soil-atmosphere exchange of N 2 O and CH 4 . So far, it is not clear how much of soil greenhouse gas (GHG) emission derives from the litter layer itself or is litter-induced. The present study investigates how the litter layer controls soil GHG fluxes and microbial decomposer communities in a temperate beech forest. Methods We removed the litter layer in an Austrian beech forest and studied responses of soil CO 2 , CH 4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 69 publications
(71 reference statements)
13
38
2
Order By: Relevance
“…Furthermore our study revealed that temperature sensitivities of litter CO 2 emissions were clearly lower than those of soil CO 2 emissions (Figure ). This is in agreement with field studies which were performed at a beech forest site in Austria [ Leitner et al , ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore our study revealed that temperature sensitivities of litter CO 2 emissions were clearly lower than those of soil CO 2 emissions (Figure ). This is in agreement with field studies which were performed at a beech forest site in Austria [ Leitner et al , ].…”
Section: Discussionsupporting
confidence: 92%
“…The litterfall represents a substantial and rather constant proportion (33.9%) of NPP (Tables and ). The C in litterfall is mostly released to the atmosphere after decay, which makes the litter pool important for understanding greenhouse gas emissions from the forest floor (Leitner et al, ). It appears that litterfall rates have increased since 2002 at an annual rate of 1.3 g C · m −2 · year −1 and NPP decreased by 5.0 g C m −2 · year −1 , although trends were not statistically significant (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely a consequence of changes in litter quantity and quality after the input of organic matter via leaf fall. In beech forests, CO 2 fluxes reduced by 30% after litter removal was found [49], suggesting a high influence of the forest floor on soil respiration. Raich and Tufekciogul [24] also point to better decomposable leaf litter and faster nutrient cycling rates under deciduous species.…”
Section: Soil Respiration and Soc Stocksmentioning
confidence: 97%
“…While the very high forest floor SOC stocks in coniferous forests might be vulnerable to disturbance or temperature increases, the SOC stocks in both forest floor and mineral soil of mixed deciduous/coniferous stands appear to be more resilient to disturbance and climate change [51]. SOC stocks are influenced by C input through root and leaf litter and rhizodeposition [24,49,52]. It has been shown that the age of carbon residues in recently fallen litter as well as in the soil of deciduous forests is lower than in coniferous forests [53], indicating a faster turnover.…”
Section: Soil Respiration and Soc Stocksmentioning
confidence: 99%
See 1 more Smart Citation